(untitled) (Bangladesh Journal of Medical Science, 2017)
Introduction: Many researches have demonstrated the effect of artificial light exposure during sleep on the circadian rhythm that controls the sleep-wake cycle. Lighting during sleep suppresses the melatonin that is responsible for the sleep-wake cycle. Consequently, this affects students academic performance and their involvement in curricular and extracurricular activities. Aims: We conducted a study to find the effects of the exposure of light during sleep on students sleep quality, level of concentration in class, academic performances and involvement in extracurricular activities. Material and methods: A cross sectional study was performed by distributing a questionnaire to 238 second year medical undergraduate students. Results: We found that 84% of the respondents usually slept with light off. Students sleeping with light on reported having a lower quality of sleep and also reported having more difficulty concentrating in class. As compared to students with lights off during sleep, those who reported sleeping with the light on also reported scoring lower marks and less extracurricular activity, Conclusion: Sleeping with lights on during sleep appears to be related to poor sleep quality, lowered level of concentration in class, lower students academic performances and less involvement in extracurricular activities. Bangladesh Journal of Medical Science Vol.16(4) 2017 p.541-544